2009
DOI: 10.7863/jum.2009.28.9.1245
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Sonography Is Effective in Detection of Soft Tissue Foreign Bodies

Abstract: High-resolution sonography is a very sensitive tool in diagnosis of soft tissue FBs. It also helps the surgeon with accurate localization, permitting easy removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
(22 reference statements)
1
28
0
2
Order By: Relevance
“…After our complete review of these articles and their reference sections and our limited reviews of other databases, we included 17 articles in this metaanalysis (Table 1). All 17 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] reported data for calculation of sensitivity; however, only 13 [23][24][25][26][27][28][29][30][31][32][33][34]36,37 reported data for calculation of specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After our complete review of these articles and their reference sections and our limited reviews of other databases, we included 17 articles in this metaanalysis (Table 1). All 17 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] reported data for calculation of sensitivity; however, only 13 [23][24][25][26][27][28][29][30][31][32][33][34]36,37 reported data for calculation of specificity.…”
Section: Resultsmentioning
confidence: 99%
“…The study with a low risk of bias in two of the categories of the quality assessment was a retrospective review of 123 cases referred to a diagnostic research facility in India conducted by Saboo et al 37 They excluded patients lost to follow-up (n = 12) and those with negative US imaging who did not undergo surgery (n = 7). When analyzing only those patients who underwent surgery, the study found sensitivity and specificity of 94.5 and 53.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Elle permet sa localisation, notamment en profondeur, par rapport aux plans superficiels. La rentabilité de l'examen est fonction de l'expérience de l'opérateur et de la formation reçue [15,16].…”
Section: Corps éTrangers Des Tissus Mous Collections Sous-cutanées Eunclassified
“…Sensitivities of up to 94-98% for ultrasound detection of both radiolucent and radiopaque foreign bodies have been reported. 2,3 In addition to its high diagnostic accuracy, ultrasound has the benefit of real-time visualisation, which can significantly improve foreign body removal and reduce complications of the procedure. 4 How accurate is emergency physician-performed PoCUS for detecting foreign bodies?…”
Section: Case Examplementioning
confidence: 99%
“…2,3 A good understanding of the sonographic characteristics of the various kinds of foreign bodies is important when correlating with the patient history, and can improve accuracy.…”
Section: Introductionmentioning
confidence: 99%